Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.ejvs.2018.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgeon's Experience on Vascular and Haemorrhagic Complications After Kidney Transplantation

Abstract: The surgeon's experience is an independent risk factor for vascular and haemorrhagic complications after KTx. Acceptable post-operative vascular and haemorrhagic complications are achieved after a minimum of 26 KTx. As a donor age of >60 years and recipient CVD are also independent risk factors for vascular and haemorrhagic complications, it is suggested that these patients should preferably be operated on by surgeons who have performed more than 26 KTx operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…5,10,11 Nevertheless, the prolonged use of aP is astonishing as both early and late thromboses are more often related to numerous other factors such as hyperacute rejection by preformed antibodies, surgical experience regarding vessel anastomoses, small vessels in either the donor graft or the recipient, which are not associated with coagulation disorders and therefore cannot be modified by anticoagulants and antiplatelets. 23 Within this context, a limited use of aP for only a few days or weeks following pediatric KTx could be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…5,10,11 Nevertheless, the prolonged use of aP is astonishing as both early and late thromboses are more often related to numerous other factors such as hyperacute rejection by preformed antibodies, surgical experience regarding vessel anastomoses, small vessels in either the donor graft or the recipient, which are not associated with coagulation disorders and therefore cannot be modified by anticoagulants and antiplatelets. 23 Within this context, a limited use of aP for only a few days or weeks following pediatric KTx could be discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Multidisciplinary evaluation, including consultation of a vascular surgeon, to evaluate the cardiovascular status of kidney transplant candidates could improve the identification of patients at risk for (cardiovascular) death and those who could potentially benefit from interventions to improve their prognosis after transplantation [5][6][7]. When screening kidney transplant candidates, evaluation generally includes traditional risk factors, as used in risk prediction scores for the general population (i.e., the Framingham score), and transplant candidate-specific risk factors, with among others chronic kidney disease-mineral bone disorder (CKD-MBD) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Transplant surgery has become more complex, especially at the vascular level due to the aging of donors and recipients [24]. Kulu et al [25] reported the young age of a surgeon as a risk factor of vascular and hemorrhagic complications after kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%